2017
DOI: 10.1371/journal.pone.0178135
|View full text |Cite
|
Sign up to set email alerts
|

"I was in the darkness but the group brought me light": Development, relevance and feasibility of the Sondela HIV adjustment and coping intervention

Abstract: Developing interventions that address psychosocial wellbeing of people living with HIV is critical to ensure strong linkages to and retention in HIV care. This paper describes the development of Sondela, an HIV adjustment and coping intervention for heterosexual men and women living with HIV, and its relevance and feasibility in the South African context. Sondela is a six three-hour, small group-based, participatory workshop series. We followed an iterative, multi-phased process of curriculum development that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Specifically, personality indirectly changes HRQoL by influencing the process of coping with illness [ 72 ] and illness appraisal [ 73 ]. Several studies conducted among PLWH showed that coping and appraisal are crucial to the success of psychosocial interventions [ 65 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, personality indirectly changes HRQoL by influencing the process of coping with illness [ 72 ] and illness appraisal [ 73 ]. Several studies conducted among PLWH showed that coping and appraisal are crucial to the success of psychosocial interventions [ 65 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several interventions have sought to address men's gender inequitable masculinities as a pathway to improve HIV prevention and treatment outcomes [15][16][17]. Many of these interventions are based on small-group participatory approaches, drawing on Freire's [18] understanding of adult education.…”
Section: Introductionmentioning
confidence: 99%
“…Although time intensive (eight 2.5-hr biweekly sessions over 4 months), the program improved resilience through positive reframing, healthy activities, social support, and coping, which had positive effects on depression, anxiety, and stress. Another intervention, the Sondela program, is an HIV coping and adjustment intervention composed of six 3-hr group sessions used to enhance psychological well-being and resilience in PLWH shortly after HIV diagnosis or starting ART (Shai et al, 2017). The Sondela intervention is designed to connect PLWH to social support and address challenges that may affect coping (e.g., depression, stress, medication adherence); a pilot study of this program showed improvements in psychosocial support and bolstered linkages and retention in HIV care (Shai et al, 2017).…”
mentioning
confidence: 99%
“…Another intervention, the Sondela program, is an HIV coping and adjustment intervention composed of six 3-hr group sessions used to enhance psychological well-being and resilience in PLWH shortly after HIV diagnosis or starting ART (Shai et al, 2017). The Sondela intervention is designed to connect PLWH to social support and address challenges that may affect coping (e.g., depression, stress, medication adherence); a pilot study of this program showed improvements in psychosocial support and bolstered linkages and retention in HIV care (Shai et al, 2017). Thus, resilience resources have been shown to be a malleable and promising intervention target in PLWH; however, little work has focused on interventions targeting older people living with long-term HIV to build resilience in the context of day-to-day stressors.…”
mentioning
confidence: 99%